Decoding Marxist Themes in A Bug's Life: A Study of Power, Exploitation, and Class Struggle - Johanes, Cayla Abielle; Miarso, Jessie Queen; Martin, Violet Ayuwandira Larasati (Yayasan Pendidikan Gereja Masehi Advent Hari Ketujuh Makarios, 2026)
This research aims to deep dive into the issues of class struggle, exploitation, and power, shown in the 1998 Pixar movie, “A Bug’s Life”, through the lens of Marxism theory. This analysis was conducted using the Marxist perspective from the book Das Capital, Volume I (1990) by Karl Marx. By using a qualitative close reading method, the data were collected through the deep observation of the cinematography and themes present, repeated viewing of scenes and narratives, plot and storyline reading based on the Marxism concepts to strengthen the arguments. Hence the findings show: 1) Symbolic Representation of Classes: The grasshoppers symbolize the bourgeoisie, or ruling class, which exploits the ants, representing the proletariat or working class, by taking their production without contributing to it, mirroring Marx's concept of workers being bound by